A new method to texture dense Mn+1AXn ceramics by spark plasma deformation. (15th January 2016) - Lapauw, T.; Vanmeensel, K.; Lambrinou, K.; Vleugels, J.
Graphical abstract: Abstract: This work explored a new method to texture M n +1 AX n phases by deforming discs of dense ceramics Maxthal 211® (nominally Ti2 AlC) and Maxthal 312® (nominally Ti3 SiC2 ) in a spark plasma facility. The disc diameter increased by 40% without crack formation. After deformation, the MAX grains exhibited clear preferential crystallographic orientation, whereby the c -axis was aligned to the compression direction. The fracture toughness increased both parallel and perpendicular to the textured top surface compared with the as-sintered materials. The onset of plastic deformation was observed near the brittle-to-plastic transformation temperature, a fact that could be associated with the change in elastic response.